ผลของการใช้รูปแบบพยาบาลพี่เลี้ยงสำหรับพยาบาลใหม่ต่อความพึงพอใจในงานและความสามารถในการปฎิบัติงาน - ทวีวัฒนา เชื้อมอญ (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
The purposes of this quasi- experimental research were to compare newly nurse graduates’ job satisfaction and job performance before and after using the nurse mentorship for newly nurse graduates model and to compare such variables after the experiment between newly nurse graduates in the experimental and control group. Research subjects consisted of 34 newly nurse graduates which were equally assigned into one experimental group and one control group. Newly nurse graduates in the experimental group worked with nurse mentors who had been trained and utilized the model for 2 months. The model, used in this experiment, was constructed by the researcher utilizing the content derived from the transcription of indepthed interview of experts. Research data was gathered by 2 research tools which were job satisfaction and job performance questionnaires. These tools were tested for content validity and internal reliability. Statistical techniques used in data analysis were mean, standard deviation and t - test. Major results of study were followed: 1. Job satisfaction and job performance of newly nurse graduates after the experiment were significantly higher than before the experimental, at the .05 level. 2. After the experiment, job satisfaction of newly nurse graduates in the experimental group was significantly higher than that in the control group, at the .05 level. 3. Before the experiment, job performance of newly nurse graduates in the control group was significantly higher than that of the experiment group. Nevertheless, after the experiment, there is no significant different between job performance of these graduates in the experiment and the control group.